The pattern of emergency department length of stay in Saudi Arabia: an epidemiological Nationwide analyses of secondary surveillance data - Alharbi, Abdullah A.; Muhayya, Mona; Alkhudairy, Reem; Alhussain, Ahmed A.; Muaddi, Mohammed A.; Alqassim, Ahmad Y.; AlOmar, Reem S.; Alabdulaali, Mohammed K. (Frontiers in Public Health, 2023)
Background. Emergency department length of stay is a vital performance indicator for quality and efficiency in healthcare. This research aimed to evaluate length of stay patterns in emergency departments across Saudi Arabia and identify predictors for extended stays. The study used secondary data from the Ministry of Health's Adaa program. Methods. Using a retrospective approach, the study examined data from the Adaa program on emergency departments' length of stay from September 2019 to December 2021. This data covered 1,572,296 emergency department visits from all regions of Saudi Arabia. Variables analyzed included quality indicators, year of visit, shift time, hospital type, and data entry method. Analysis was done using multiple linear regression. Results. The study found that the median length of stay was 61 minutes, with significant differences among related predictors. All associations were significant with a P-value less than 0.001. Compared to 2019, the length of stay was notably shorter by 28.5% in 2020 and 44.2% in 2021. Evening and night shifts had shorter length of stay by 5.9% and 7.8% respectively, compared to the morning shift. Length of stay was lower in winter, summer and fall compared to spring. Patients in levels I and II of the Canadian Triage and Acuity Scales had longer stays than level III, with level I reaching an increase of 20.5%. Clustered hospitals had a higher length of stay compared to non-clustered ones. Pediatric hospitals had a 15.3% shorter stay compared to general hospitals. Hospitals with data entered automatically had a 14.0% longer stay than those entered manually. Patients admitted to the hospital had a considerably longer length of stay, 54.7% longer compared to non-admitted patients. Deceased patients had a 20.5% longer stay than This is a provisional file, not the final typeset article patients discharged alive. Conclusions. Data at the national level identified several predictors of prolonged emergency department length of stay in Saudi Arabia, including shift, season, severity level, and hospital type. These results underline the necessity of continuous monitoring and improvement efforts in the emergency department, in line with policy initiatives aiming to enhance patient outcomes in Saudi Arabia.